Isolation, antimicrobial activity of myxobacterial crude extracts and identification of the most potent strains - Charousová, Ivana; Medo, Juraj; Javoreková, Soňa (Archives of Biological Sciences, 2017)
Broad spectrum antimicrobial agents are urgently needed to fight frequently occurring multidrug-resistant pathogens. Myxobacteria have been regarded as “microbe factories” for active secondary metabolites, and therefore, this study was performed to isolate two bacteriolytic genera of myxobacteria, Myxococcus sp. and Corallococcus sp., from 10 soil/sand samples using two conventional methods followed by purification with the aim of determining the antimicrobial activity of methanol extracts against 11 test microorganisms (four Gram-positive, four Gram-negative, two yeasts and one fungus). Out of thirty-nine directly observed strains, 23 were purified and analyzed for antimicrobial activities. Based on the broth microdilution method, a total of 19 crude extracts showed antimicrobial activity. The range of inhibited wells was more important in the case of anti-Gram-positive-bacterial activity in comparison with the anti-Gram-negative-bacterial and antifungal activity. In light of the established degree and range of antimicrobial activity, two of the most active isolates (BNEM1 and SFEC2) were selected for further characterization. Morphological parameters and a sequence similarity search by BLAST revealed that they showed 99% sequence similarity to Myxococcus xanthus − BNEM1 (accession no. KX669224) and Corallococcus coralloides – SFEC2 (accession no. KX669225). As these isolates had antimicrobial activity, they could be considered for use in the development of antibiotics for pharmaceutical use. https://doi.org/10.2298/ABS161011132C Received: October 11, 2016; Revised: November 14, 2016; Accepted: November 18, 2016; Published online: December 14, 2016 How to cite: Charousová I, Medo J, Javoreková S. Isolation, antimicrobial activity of myxobacterial crude extracts and identification of the most potent strains. Arch Biol Sci. 2017;69(3):561-8.